A controlled study of cognitive psychotherapy in schizophrenia - Zain, Azhar (2002)
A number of psychological approaches to alleviating psychotic symptoms have been reported in the literature such as social reinforcements (1),time-out (2),punishment (3),assertive training (4),exercise (5),stimulus control (6),self-instruction (7),thought stopping (8),control of stitnulus input (9),biofeedback (1 0),and self-control (11) among others.The first part of this research paper describes an experiment that makes use of cognitive psychotherapy to treat chronic drug resistant delusions (more than 12 years duration) in two patients with schizophrenia.The positive response of both patients with the absence of symptom replacement and maintenance of response at 18 months followup,seem to imply that this technique is useful and more effort needs to be invested into this new area of psychotherapy for psychosis.